Keamanan Sistem Informasi Pemilu Melalui Computer Security Incident Response Team (Csirt) Pemilu Serentak 2024 - Ricky Febriansyah; Ana Husnayanti (Jurnal Ilmu Politik dan Studi Sosial Terapan, 2024)
The General Elections Commission together with the National Cyber ​​and Crypto Agency (BSSN)  formed a Computer Security Incident Response Team (CSIRT) to secure information systems supporting elections  from cybercrimes. With a SWOT      (Strength, Weakness, Opportunities, Threats) analysis approach, this study aims to determine: 1). Causes of information systems  are often attacked; 2). obstacles to preventing election information system crimes; 3). As a result of unstoppable cyber attacks;  4). KPU-CSIRT implementation solutions; 5). Potential problems with the implementation of KPU-CSIRT; and 6). CSIRT implementation strategy.  This study uses a qualitative approach with data collection methods through observation and document study. The results of research on  election information systems are often attacked due to the weakness of KPU cyber security and human factors. the implementation of CSIRT  faces several potentials such as human resources, budget and infrastructure, the threat of election and election hoax news, especially  the information system output that is applied, the implementation of the General Election Commission Regulation Number 5 of 2021 concerning  the Implementation of an Electronic-Based Government System can be a reference in the implementation of CSIRT. The KPU-CSIRT strategy can  be carried out from the KPU to the Provincial KPU and Regency/Regional KPU even at the ad hoc level. It is hoped that with this program,  the application of the information system developed by the KPU can maintain public confidence in the legitimate election results.